2016
DOI: 10.1371/journal.pone.0157875
|View full text |Cite
|
Sign up to set email alerts
|

A Probiotic Adjuvant Lactobacillus rhamnosus Enhances Specific Immune Responses after Ocular Mucosal Immunization with Chlamydial Polymorphic Membrane Protein C

Abstract: Recent advances in the development of chlamydia vaccines, using live-attenuated or ultraviolet light-inactivated chlamydia, are paving the way for new possibilities to oppose the societal challenges posed by chlamydia-related diseases, such as blinding trachoma. An effective subunit vaccine would mitigate the risks associated with the use of a whole-cell vaccine. Our rationale for the design of an efficient subunit vaccine against Chlamydia trachomatis (Ct) is based on the membrane proteins involved in the ini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
(39 reference statements)
1
10
0
Order By: Relevance
“…In addition, we also found that Lactobacillus salivarius group exhibited an enhanced immune response after immunization compared to control group in chickens without cy treatment. This is consistent with previous results that Lactobacillus can be used as immune adjuvant to enhance antigen-specific immune responses (30,31).…”
Section: Discussionsupporting
confidence: 94%
“…In addition, we also found that Lactobacillus salivarius group exhibited an enhanced immune response after immunization compared to control group in chickens without cy treatment. This is consistent with previous results that Lactobacillus can be used as immune adjuvant to enhance antigen-specific immune responses (30,31).…”
Section: Discussionsupporting
confidence: 94%
“…In addition to working with C. muridarum , Karunakaran et al [47] also immunized mice with a polyvalent vaccine formulated with PmpEFGH from C. trachomatis serovar D and three MOMPs from serovars D, J and F. The mice were challenged transcervically and, as determined by the number of C. trachomatis serovar D IFU recovered, animals vaccinated with the combination of the four Pmps and the three MOMPs, were better protected than those vaccinated with either the Pmps, or the three MOMPs alone. Interestingly, Inic-Kanada et al reported that PmpC of C. trachomatis serovar B elicited partial protection in guinea pigs against an ocular challenge with C. caviae [48, 49]. …”
Section: Discussionmentioning
confidence: 99%
“…The sequence identity of PmpC for the E, F and Da serovars is 98–100% and therefore, inclusion of this antigen in a human vaccine could have a major impact on the prevalence of chlamydial infections. In support of the possibility of cross-serovar protection induced by PmpC, Inic-Kanada et al [48] have recently shown that mice vaccinated in the ocular mucosa with PmpC from C. trachomatis serovar E developed humoral and cell mediated immune responses that cross-reacted with serovar B.…”
Section: Discussionmentioning
confidence: 99%
“…Development of immunity by Lactobacillus strains could associated with lymphoid tissues that regulate the immune response of their hosts for example Lactobacillus helveticus R389, Lactobacillus rhamnosus HN001 and Lactobacillus acidophilus HN017 [97,[166][167][168] have been reported to have the ability to improve the immune system of their host. The mechanism of this improvement is thought to be caused by the consequence of the Lactobacillus strains because of the: total serum protein, globulin, interferon-gamma, prostaglandin E production, albumin, tumor necrosis factor, interleukin-1 (IL-1), interleukin-2 (IL-2), interleukin-4 (IL-4), interleukin-6 (IL-6), and lymphocytes proliferation.…”
Section: Discussionmentioning
confidence: 99%